The epidemiology of cryptosporidiosis: application of experimental sub-typing and antibody detection systems to the investigation of water-borne outbreaks - McLauchlin, J; Casemore, D P; Moran, S; Patel, S (Folia parasitologica, 1998)
A technique based on the analysis of banding patterns obtained by SDS-PAGE Western-blotting of an oocyst wall antigen obtained from faeces has been evaluated to subtype Cryptosporidium parvum Tyzzer, 1912. This technique appears to have sufficient stability to recognise multiple types of this parasite. A similar Western-blotting technique has also been used to assess antibody responses to cryptosporidial antigens in human sera. Two systems were developed: one against three antigens of apparent molecular weights 6, 14 and 17 kDa; the second against oocyst wall antigens of apparent molecular weights 57, 69, 75, 89, 128, 151 and 173 kDa. Antibodies to three antigens of apparent molecular weights 6, 14 and 17 kDa were most successful as diagnostic markers in that they were found in > 88% of convalescent phase sera from confirmed cryptosporidiosis patients and were uncommon (> or = 7%) in control subjects. Faecal samples from human and animal sporadic cases yielded a wide range of cryptosporidial antigen banding patterns. Samples from patients in a water-borne outbreak in South Devon (England) in 1995 also yielded a wide range of banding patterns including members within individual household family groups. These results are in contrast with those from samples collected from other defined geographical areas, including some from a second water-borne outbreak where much more homogeneous banding patterns were obtained. Sera collected for other purposes from apparently uninfected individuals 9 months after the South Devon 1995 outbreak were examined. Antibodies to the three antigens of molecular weights 6, 14 and 17 kDa were detected in 32-49% of individuals resident in the outbreak water supply area, and in 15-21% of those resident in an adjacent water supply area. The significance of these findings is discussed in relation to data obtained from epidemiological field studies.
Keywords: Anglie; Cryptosporidiosis; Feces; antigeny protozoální; Animals; Antibodies, Protozoan; Humans; Electrophoresis, Polyacrylamide Gel; Cryptosporidium parvum; protilátky protozoální; Antigens, Protozoan; feces; kryptosporidióza; Disease Outbreaks; zvířata; voda; western blotting; England; Water; Blotting, Western; epidemický výskyt choroby; elektroforéza v polyakrylamidovém gelu; lidé